PENGARUH MOTIVASI TERHADAP GAIRAH KARJA GURU PADA SMP NEGERI 2 BELITANG OKUTIMUR - Setia Kurniawan (Jurnal AKTUAL, 2020)
Teachers are learning agents who have a very important role in educating the nation to achieve educational goals. As a learning agent, teachers must have a passion for work in carrying out their duties. If they do not have a passion for work, how can they guide their students to achieve the specified minimum learning competencies? Therefore, work passion is a problem that needs to be given a solution through motivation. This study aims to determine whether motivation has an effect on work passion, with the object of research being the teachers at SMP Negeri 2 Belitang OKU Timur. The hypothesis proposed is that "There is a significant influence between motivation on the morale of teachers at SMP Negeri 2 Belitang  OKU Timur". Data collection techniques by means of library research, field, and questionnaires. While the analytical tools used are qualitative analysis and quantitative analysis. Based on the calculation, it turns out that r = 0.797 after being consulted with a conservative standard, it turns out that 0.797 lies between 0.600 - 0.799 which mean it belongs to a strong correlation or influence. Then to answer the hypothesis proposed in the previous chapter has a relationship or not, then tested by testing the hypothesis and obtained t = 3.6393 and "t" table obtained 1.860. It can be concluded that the "t" count is greater than the "t" table, namely 3.6393> 1.860. Thus the hypothesis can be accepted (Ha is accepted and Ho is rejected). As for the suggestions that can be given to achieve optimal goals from the agency, it is better if a leader gives encouragement or motivation to teachers in the agency environment so that teachers can work in accordance with what is expected by the agency.